Assessment of bacterial contamination of the beef at the Tanzania selected abattoirs - Yasir Hemed Rashid; Davis Naboth Chaula; Ismail Said Selemani (Journal of Applied Animal Research)
The bacterial contamination of meat carcasses occurs mainly during processing and manipulation. Due to the abundance of nutrients in meat may encourage the growth of microorganisms and the animal transmission of harmful bacteria, meat is regarded as food with a high risk of contamination. A cross-sectional study was carried out in two Abbatoirs in Tanzania, Morogoro Municipality and NARCO, and bacteriological analysis was performed to determine the level of bacterial contamination in beef (chuck beef, sirloin beef and ground beef). Ninety samples from different beef were collected from three breeds (cows) (Ancole, Boran and Gogo) transferred without undue delay to the Laboratory of Food Science of Sokoine University of Agriculture, and subjected to bacteriological examination. The results specified that mean values of Total Plate Count (TPC), at the chuck beef, sirloin beef and round beef were 6.09 ± 0.20, 5.93 ± 0.18 and 5.87 ± 0.18 log cfu/g respectively. Though mean values of Salmonella Count at the previous regions were 1.30 ± 0.19, 1.35 ± 0.20 and 0.93 ± 0.18 log cfu/g, respectively, while mean values of total E.coli count were 1.07 ± 0.14, 1.10 ± 0.12 and 2.03 ± 0.15 log cfu/g, respectively, mean values of total Staphylococcal count were 4.34 ± 0.15, 3.62 ± 0.2 and 4.80 ± 0.14 log cfu/g, respectively. The breeds were not significantly different to all microbes examined. The samples concealed high counts of microorganisms.